(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2014)
The study aimed analyzes according to Behavior Analysis view the maternal report about their children’ behavior with chronic skin disease. Thirty two mothers of children between 6 and 12 years old with chronic skin diseases were interviewed. Mothers described their children as anxious, socially isolated, showing somatic complains, irritability, easily staying bore and hurt, and difficulty to follow medical treatment. Mothers reported guilt, hopelessness and concerns about their children condition, and tiredness by not being able to manage children’ compliance behavior to the treatment. Behavioral analysis of the reports, conducted by describing contingencies and by formulating functional hypotheses, identified situations or aversive conditions (reaction to the diagnosis, identification of factors responsible for the onset and/or worsening symptoms, treatment adherence and prejudice) in which these feelings were reported and its consequences for mothers and their children